Biomechanical Comparison of Cortical Lag Screws and Cortical Position Screws for Their Generation of Interfragmentary Compression and Area of Compression in Simulated Lateral Humeral Condylar Fractures - Fuchter, Lucy M.; Wills, Dan; Walsh, William R.; Newman, Mark; Tan, Chris (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objective The aim of this study was to compare the interfragmentary compressive force and area of compression generated by cortical screws inserted as either a lag screw or position screw in simulated lateral humeral condylar fractures.Study Design Ex vivo biomechanical study.Materials and Methods Thirteen pairs of cadaveric humeri from skeletally mature Merinos with simulated lateral humeral condylar fractures were used. Pressure sensitive film was inserted into the interfragmentary interface prior to fracture reduction with fragment forceps. A cortical screw was inserted as a lag screw or a position screw and tightened to 1.8Nm. Interfragmentary compression and area of compression were quantified and compared between the two treatments groups at three time points.Results After fracture reduction using fragment forceps (Time point 1: T1), there was no significant difference in interfragmentary compression and area of compression between the two treatments. A combination of fragment forceps and a cortical screw inserted as a lag screw (Time point 2: T2) produced significantly greater interfragmentary compression and area of compression compared with the same screw inserted as a positional screw. After removal of the fragment forceps, leaving only the cortical screw (Time point 3: T3), both the interfragmentary compression and area of compression remain significantly greater in the lag screw group.Conclusion Lag screws generate a greater force of compression and area of compression compared with position screws in this mature ovine humeral condylar fracture model.
Keywords: position screw; lag screw; interfragmentary compression; lateral humeral condylar fractures; area of compression